Education for poverty eradication: Malaysian government and non-governmental organizations initiatives - Md Saad, R.; Idris, N.; Loh, S.C.; Subramiam, S.; Mohd Nor, N. (2008)
As a developing country, it is a concern that poverty is still an issue in Malaysia. Among effects of poverty in society are failures of the poor children to receive a good education. This will affect their future as education is an important tool of sustainable and equitable development. As a responsible government in eradicating poverty, the Malaysian government, through its various agencies and authorities, is involved in attempting to determine the issues. This effort also receives support from various Non-Government Organisations (NGOs). The main focus in this effort is to provide educational opportunities and facilities for the children in poverty. Through education, they can become skilled and consolidate positive change in their attitudes towards poverty. The main agenda is to increase access at all educational levels (kindergartens, primary, secondary and university) for poor communities. The initiatives provided for them are in the form of financial and educational support systems. This paper will discuss the initiatives that are part of the efforts to democratize education in Malaysia for more efficient poverty eradication.